(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to show the impact of the dimensions of organizational transparency that can be performed as an independent variable represented by (accountability, information, empowerment, performance evaluation, transparency) and the degree of arrangement of those dimensions according to their priority and importance in enhancing the efficiency of tax performance as the approved variable, as the research problem was identified by raising questions centered on the nature of the impact relationship between the research variables, and for that a hypothetical scheme and one main hypothesis were developed from which five sub-hypotheses emerge, and were subjected to statistical tests Through the statistical program (SPSS v.26) in calculating (weighted arithmetic mean, standard deviation, coefficient of variation, exploratory factor analysis and simple linear regression analysis, determination coefficient R2 to show its validity, the descriptive analytical approach has been adopted, and the questionnaire was relied on as a main tool in collecting data from the sample of (103) officials in the General Tax Authority, and the research reached a number of results, the most important of which is that there is a significant impact of the dimensions of organizational transparency on providing an appropriate tax environment in society. Contributes to the efficiency of tax performance.